Incidencia de la variabilidad hidrológica en la morfología de cauces del arroyo Claromecó (Buenos Aires, Argentina) - García Martínez, Belén; Carbone, María Elizabeth; Piccolo, Cintia; Perillo, Gerardo (Geographicalia, 2015)
This paper focuses on the hydrological variability of the Claromecó Creek as well as on the morphology of both its courses and the banks of the main course and major affluents. The outcome of this research helped determine its rainfall pattern as oceanic though with a very small irregularity and runoff rate and detect the processes of excavation, subsidence and fluvial incision in the main course. These processes have been reactivated by the channelling and straightening of the Claromecó fluvial network.